Fabrication and characteristics of porous germanium films - Jing, Chengbin (Sci Technol Adv Mater, 2009)
Porous germanium films with good adhesion to the substrate were produced by annealing GeO(2) ceramic films in H(2) atmosphere. The reduction of GeO(2) started at the top of a film and resulted in a Ge layer with a highly porous surface. TEM and Raman measurements reveal small Ge crystallites at the top layer and a higher degree of crystallinity at the bottom part of the Ge film; visible photoluminescence was detected from the small crystallites. Porous Ge films exhibit high density of holes (10(20) cm(−3)) and a maximum of Hall mobility at ∼225 K. Their p-type conductivity is dominated by the defect scattering mechanism.